2008
DOI: 10.1007/s11046-007-9085-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a GFP-Expressing Aspergillus flavus Strain to Study Fungal Invasion, Colonization, and Resistance in Cottonseed

Abstract: Cotton bolls were inoculated with a green fluorescent protein (GFP)-expressing Aspergillus flavus (strain 70) to monitor fungal growth, mode of entry, colonization of cottonseeds, and production of aflatoxins. The GFP strain and the wild-type did not differ significantly in pathogen aggressiveness as indicated by similar reductions in inoculated locule weight. GFP fluorescence was at least 10 times higher than the blue green yellow fluorescence (BGYF) produced in response to infection by A. flavus. The GFP pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 26 publications
(27 reference statements)
3
37
0
Order By: Relevance
“…Furthermore, the gfp gene is useful to study functionality of candidate genes related to drought stress as demonstrated in barley (Nagy et al, 2011). The gfp expressing Aspergillus flavus fungus was also used to study fungal infection in cottonseed (Rajasekaran et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the gfp gene is useful to study functionality of candidate genes related to drought stress as demonstrated in barley (Nagy et al, 2011). The gfp expressing Aspergillus flavus fungus was also used to study fungal infection in cottonseed (Rajasekaran et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The stable transmission of the cpo-p gene was further confirmed by Southern blot and expression analysis of progeny from one transgenic line. To our knowledge, the bacterial cpo-p gene has been thoroughly studied in only two transgenic plant species, tobacco and cotton, with a vector carrying cpo-p and kanamycin resistance genes (Jacks et al , 2004Rajasekaran et al 2000Rajasekaran et al , 2008. We have previously shown that a codonmodified Bt cryIA(c) gene, which was introduced into three peanut cultivars (Singsit et al 1997), has potential to provide a barrier to fungal entry by reducing insect damage to peanut tissue.…”
Section: Resultsmentioning
confidence: 99%
“…All of these elements were subcloned into the plasmid vector pBlueScript-SK (Stratagene) to produce the vector gpd-EGFP (Rajasekaran et al 2008). Plasmid gpd-EGFP was cotransformed with the vector pSL82 harboring the A. parasiticus nitrate reductase (niaD) gene into the niaD mutant of A. flavus 70.…”
Section: In Vitro Bioassay Of Antifungal Activity In Transgenic Tissumentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent use of reporter genes was performed on cotton using a green fluorescent protein reporter; a GFP-expressing A. flavus strain to successfully monitor fungal growth, mode of entry, colonization of cottonseeds, and production of aflatoxins [38]. This strain provides for an easy, potentially non-destructive, rapid and economical assay which can be done in real time, and may constitute an advance over GUS transformants.…”
Section: Comparing Fungal Growth To Toxin Productionmentioning
confidence: 99%